Consumer's preferences among low-calorie food alternatives in casual dining restaurants. Issue 8 (26th June 2021) - Sun, Xiaodi; Almanza, Barbara; Behnke, Carl; Ghiselli, Richard; Byrd, Karen
Abstract : Purpose: This study aims to examine consumers' preferences among four calorie-reducing approaches – resizing, reformulation, substitution and elimination – and to understand what motivates consumers to order low-calorie food using the theory of planned behavior (TPB) as a model. Design/methodology/approach: A conceptual model was developed based on the TPB with an additional construct of food choice motives. A total of 467 responses were collected. Descriptive statistics, multiple regression and ANOVA were used in the data analysis. Findings: Consumers have a clear preference for substitution and elimination. The pattern that ingredients with higher calories were modified at a higher priority indicated that consumers might improve food decisions based on calorie information. Practical implications: Restaurants should allow substitution or elimination of certain ingredients from menu items. Including more low-calorie sides will cost restaurants less than changing the main dish. A menu item on an entrée form is more amenable to modification for decreased calorie content as consumers have high taste expectations for popular traditional foods (e.g. burgers and pizza). Originality/value: This is the first study to investigate consumers' preferences among the four popular calorie-reducing approaches. A novel "Build Your Own Meal" approach was used in the questionnaire to allow the participants to choose from more than 150 ingredients, which compensated for personal preferences, thus mitigating possible limitations associated with studies of this kind, and was a good indicator of the participants' actual ordering behavior.